The Compliance Chronic Renal Failure Patient on Restrictions Liquids in Hemodialysis Therapy - Endang Sri P Ningsih; Agus Rachmadi; Hammad Hammad (Universitas Airlangga, 2012)
Introduction: Nonadherence is a rampant problem among patients undergoing dialysis and can impact multiple aspects of patient care, including medications, and treatment regimens as well as dietary and fluid restriction. The purpose of this descriptive correlative research, on hemodyalysa patient with chronic renal failure was to know the influencing factors of compliance patient to fluid restriction.Methods: This study used descriptive correlative design, Data was analysed by using distibution frequency and chi square for analysys relation between variable.Results: The result revealed there were nor significant statistic difference at p > 0.05 between age, gender, education level, frequency of hemodyalysa and health education from nurse to compliance patient to fluid restriction (p = 0.647; p = 0.717; p = 0.345; p = 0.774; p = 0.273).Conclusion: Level of patient adherence to therapy not influenced by demographi factor but by the quality of interaction health workers and other factors. This study recommended for further analysis of the factors that influence the level of compliance of the patient as psychological factors (belieft , motivation), socio-economic, and social support.